2017
DOI: 10.5114/jcb.2017.66588
|View full text |Cite
|
Sign up to set email alerts
|

The use of trans-applicator intracavitary ultrasonography in brachytherapy for cervical cancer: phantom study of a novel approach to 3D image-guided brachytherapy

Abstract: PurposeTo assess the feasibility of applying trans-applicator intracavitary ultrasonography to image-guided brachytherapy for cervical cancer.Material and methodsFor this experiment, a phantom was created and included a polyethylene tube, intended to simulate a tandem applicator, which was inserted into chicken meat and embedded in agar, along with magnetic resonance imaging (MRI)-compatible ovoid applicators. Three-dimensional images of the phantom were obtained using computed tomography (CT), MRI (T2-weighte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In this study, local control at 3 years of 86%, overall survival of 75% and a cause-specific survival of 79% are reported. The use of transrectal ultrasound to guide treatment has also been described [ 8 , 9 ], as well as the experimental use of an internal transducer, through the applicator, for proper tumour delineation and subsequent planning [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, local control at 3 years of 86%, overall survival of 75% and a cause-specific survival of 79% are reported. The use of transrectal ultrasound to guide treatment has also been described [ 8 , 9 ], as well as the experimental use of an internal transducer, through the applicator, for proper tumour delineation and subsequent planning [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…86 Many authors have shown the feasibility of US assisted cervix BT compare to MRI. 81,[87][88][89][90] Some studies have been presented supporting its use in terms of clinical outcomes of patients undergoing intracavitary BT based on US imaging, showing similar findings that MRI based procedures, following GEC ESTRO recommendations. 81,91 At the moment, although recent studies support the use of US for contouring HR-CTV for IGABT of cervical cancer, [92][93][94] its exclusive use in the reconstruction process has not yet been implemented in the case of complex and interstitial BT.…”
Section: Recent and Future Prospectsmentioning
confidence: 98%